Pengaruh Promosi Media Sosial Terhadap Keputusan Pembelian Produk Sosis Solo Aneka Rasa - Purnamasari, Pupung; Irawan, Fajrul; Rahmawati, Sherly; Holivah, Lilis (Teewan Journal Solutions, 2025)
This study aims to analyze the effect of promotion through social media on purchasing decisions for Sosis Solo Aneka Rasa products. Promotion through social media has become one of the important marketing strategies for small and medium enterprises in increasing sales and competitiveness in the digital era. The research method used is a quantitative approach with data collection techniques in the form of questionnaires distributed to 30 respondents, namely consumers who have purchased Sosis Solo Aneka Rasa products. Data analysis was carried out using simple linear regression to test the relationship between promotional intensity on social media, attractiveness of promotional content, and trust in products with purchasing decisions. The results showed that promotion through social media significantly influenced consumer purchasing decisions. The attractiveness factor of promotional content has the greatest contribution in influencing purchasing decisions, followed by promotional intensity and trust in products. These findings indicate the importance for businesses to design creative, attractive, and reliable social media promotion strategies to encourage consumer interest and purchasing decisions. This research contributes to the development of effective digital marketing strategies for small and medium enterprises, especially in utilizing social media to increase sales.